La imagen conceptual de la alegría reflejada en los fraseologismos españoles y polacos - Adamiczka, Joanna (Neophilologica, 2012)
The aim of the research presented in the article is to reconstruct the conceptual image of joy reflected in the Spanish and Polish fixed expressions. The study is based on the theory of the linguistic image of the world and on the cognitive theory of metaphor. The analysis allows the formation of hypothesis about the way in which the Spanish and Polish language communities understand the idea of joy and shows that there are both similarities and differences between the conceptual images of this emotion reflected in the languages in question. In both languages the joy is conceptualized by means of the references to its prototypical causes, experiences, external expressions, internal symptoms and to other phenomena associated with it and not related to the emotional situation. Furthermore, in both languages, the joy is conceptualized with the use of the same conceptual metaphors: JOY IS LIGHT, JOY IS INTERNAL GROWTH, JOY IS LIGHTNESS, JOY IS UP. In relation to the more specific level of the conceptualization, both similarities and differences have been observed. For example, in both languages the joy is associated with the childhood, only in the Spanish language it is associated with the Easter, while only in the Polish language, with birds.